Central Nervous System Medication Burden and Serious Falls in Older Nursing Home Residents. Issue 6 (2nd February 2017) - Hanlon, Joseph T.; Zhao, Xinhua; Naples, Jennifer G.; Aspinall, Sherrie L.; Perera, Subashan; Nace, David A.; Castle, Nicholas G.; Greenspan, Susan L.; Thorpe, Carolyn T.
Abstract : Objectives: To examine the association between CNS medication burden and serious falls in those with a recent fall history. Design: Nested‐case control study; cases matched to four controls by age, gender, and date. Setting: US nursing homes. Participants: 5, 556 residents age ≥65 with a recent fall history admitted to a nursing home between 1/1‐9/30/2010 and followed until discharge, death, or December 31, 2010. Measurements: Outcome was serious falls as per Medicare Part A and B ICD/CPT codes. CNS burden, from Medicare Part D data, was calculated by dividing the daily dose of each CNS agent (i.e., specific antidepressants, antiepileptic, antipsychotic, benzodiazepine and opioid receptor agonists) received during the 6 days prior to the index (outcome) date by the minimum effective geriatric daily dose and summing the results across medications. Results: There were 367 cases and 1, 468 matched controls. Those taking 3 + CNS standardized daily doses were more likely to have a serious fall than those not taking any CNS medications (Adjusted Odds Ratio 1.83; 95% confidence interval 1.35–2.48). There was no significant difference in fall risk for residents taking >0 to <3 CNS standardized daily doses compared to residents taking no CNS medications (Adjusted Odds Ratio 0.85; 95% CI 0.63–1.15). Conclusion: CNS medication burden, approximately 3 + standardized daily doses, was associated with an increased risk of serious falls in nursing home residents with recent fall. Clinicians should be vigilant for opportunities to discontinue or decrease the doses of individual CNS medications and/or consider non‐pharmacological alternatives. Such interventions that reduce use of CNS medications in nursing homes could reduce fall rates but further research is needed to confirm this.